2000
DOI: 10.1161/01.res.87.12.1133
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Induced Vascular Hypertrophy Is Accompanied by Activation of Na + -H + Exchange and Prevented by Na + -H + Exchange Inhibition

Abstract: Abstract-Vascular disease often involves vessel hypertrophy with underlying cellular hypertrophy or hyperplasia.Experimental diabetes stimulates hypertrophy of the rat mesenteric vasculature, and we investigated the hypothesis that this hypertrophy is associated with activation of Na ϩ -H ϩ exchange (NHE) activity. We measured the NHE activity in isolated, intact blood vessels from control and streptozotocin-induced diabetic adult rats using concurrent myography and fluorescence spectroscopy. The role of inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 38 publications
(50 reference statements)
2
24
0
1
Order By: Relevance
“…We have reported previously that inhibitors of AGE formation as well as cariporide (an inhibitor of a sodium/ hydrogen exchanger) can attenuate the development of diabetic complications in a rat model (55). It remains to be determined if this relates to a central role of ERM proteins that not only bind AGEs but also NHERF 1 and 2 (56) and, thus, modulate sodium/hydrogen exchangers.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported previously that inhibitors of AGE formation as well as cariporide (an inhibitor of a sodium/ hydrogen exchanger) can attenuate the development of diabetic complications in a rat model (55). It remains to be determined if this relates to a central role of ERM proteins that not only bind AGEs but also NHERF 1 and 2 (56) and, thus, modulate sodium/hydrogen exchangers.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, altered tissue acidification in diabetes may contribute to the enhanced vasorelaxant effect of H 2 S. It has been demonstrated that elevated extracellular glucose concentrations regulates the Na + /H + exchanger activity in vascular smooth muscle cells (Williams and Howard 1994). Furthermore, increased activity of Na + /H + exchanger have been proposed for the altered regulation of intracellular pH in mesenteric vasculature in diabetes (Jandeleit-Dahm et al 2000). Therefore, altered intracellular pH of vascular smooth muscle cells in diabetes may cause the enhanced vasorelaxant effect of H 2 S in diabetic arteries.…”
Section: Discussionmentioning
confidence: 99%
“…HOE694, HOE642 or cariporide, and EMD85131) have been developed that inhibit the NHE isoforms with a similar rank order but over a larger concentration range (3-4 orders of magnitude) (15)(16)(17)(18). The more selective binding properties of these compounds for NHE1 have been exploited therapeutically as effective agents in the treatment of cardiac ischemia and reperfusion injuries (17)(18)(19)(20)(21)(22) and may prove beneficial in the prevention of diabetes-induced vascular hypertrophy (23). More recently, a preferential antagonist (S3226) of NHE3 has been synthesized that may also facilitate functional studies of this isoform in renal and intestinal epithelia (24,25).…”
Section: Namentioning
confidence: 99%